Size Selectivity in Heterolanthanide Molecular Complexes with a Ditopic Ligand. Issue 3 (24th November 2022) - Bellucci, Luca; Fioravanti, Lorenzo; Armelao, Lidia; Bottaro, Gregorio; Marchetti, Fabio; Pineider, Francesco; Poneti, Giordano; Samaritani, Simona; Labella, Luca
Abstract: The similar reactivity of lanthanides generally leads to statistically populated polynuclear complexes, making the rational design of ordered hetero‐lanthanide compounds extremely challenging. Here we report on the site selectivity in hetero‐lanthanide tetranuclear complexes afforded by the relatively simple ditopic pyterpyNO ligand (4'‐(4‐pyridil)‐2, 2':6', 2"‐terpyridine N ‐oxide). The sequential room temperature reaction of RE2 (tta)6 (pyterpyNO)2 (where RE=Y, (1) ; Eu, (2 ), Dy, (3 ) Htta=2‐thenoyltrifluoroacetone) with La(tta)3 dme (dme=dimethoxyethane) yielded Y2 La2 (tta)12 (pyterpyNO)2 (4 ), Dy2 La2 (tta)12 (pyterpyNO)2 (5 ) and Eu2 La2 (tta)12 (pyterpyNO)2 (6 ). Single crystals X‐ray diffraction studies showed that 4, 5 and 6 are isostructural, featuring a tetranuclear structure with two different metal coordination sites with coordination numbers 8 (CN8) and 9 (CN9). The two smaller cations are mainly bridged by the O ‐donor atoms of the NO groups of two pyterpyNO ligands (CN8), while the larger lanthanum centres are bound by a terpyridine unit (CN9). Size selectivity has been studied with structural and magnetic studies in the solid state and through 19 F NMR and photoluminescence studies in solution, showing a direct dependence on the difference of ionic radii of the ions and yielding a 91 % selectivity for 4 . Furthermore, 19 F NMR, X‐ray and PL studies pointed out that the nature of the product is independent from the synthetic route for compound Eu2 Y2 (tta)12 (pyterpyNO)2 (7 ), keeping the ion selectivity also for a self‐assembly reaction. Unexpectedly, these studies have evidenced that selectivity is not exclusively governed by electrostatic interactions related to size dimensions. Abstract : A size selectivity in the coordination of different lanthanides ions to the two donor sites of the ditopic pyterpyNO ligand has been evidenced in heteronuclear complexes of formula RE2 RE*2 (tta)12 (pyterpyNO)2, where smaller (larger) ions normally display a higher affinity for the eight (nine)‐coordinated oxygen (nitrogen) site. The present results, obtained in solution and in the solid state with a multi‐technique approach (X‐ray diffraction, 19 F NMR, magnetometry and photoluminescence), are independent of the employed synthetic route.